Microsoft Visual C♯ 2013 Step by Step. - Sharp, John, 1964- (Step by step (Redmond, Wash.), 2013)
Expand your expertise--and teach yourself the fundamentals of Microsoft Visual C♯ 2013. If you have previous programming experience but are new to Visual C♯ 2013, this tutorial delivers the step-by-step guidance and coding exercises you need to master core topics and techniques.